Diabetic neuropathy: a mechanism of TRPV1 sensitisation and the treatment with Vascular Endothelial Growth Factor-A165b (VEGF-A165b) - Bestall, Samuel (2017)
Diabetic neuropathy affects up to 50% of diabetic patients and commonly presents as neuropathic pain. Streptozotocin (STZ) injected type 1 diabetic rats exhibit thermal hypersensitivity and this is caused by the sensitization of transient receptor potential vanilloid 1 (TRPV1) on DRG neurons.Thermal hypersensitivity is ameliorated in STZ diabetic rats with the systemic treatment of vascular endothelial growth factor-A165b (VEGF-A165b). This thesis investigated the role of the activation of the receptor for advanced glycated end products (RAGE) on the sensitization of TRPV1 on DRG neurons and determined the effects of VEGF-A165b on this mechanism. Capsaicin-evoked TRPV1 activity was measured in DRG neurons from adult STZ diabetic rats to determine a sensitization effect and these effects were modeled in vitro by exposing DRG neuronal cultures from naïve rats to hyperglycemic conditions.